Penerapan Metode Visekriterijumsko Kompromisno Rangiranje (VIKOR) Dalam Seleksi Kepala Gudang - Satria, M. Najib Dwi (CV. Keranjang Teknologi Media, 2023)
The selection of warehouse heads is a critical step in maintaining the smooth operation of a company. The head of the warehouse has a central role in managing and overseeing all aspects of storage, distribution, and inventory management of goods. This study aims to apply the Visekriterijumsko Compromise Rangiranje (VIKOR) method in the selection of Warehouse Heads using criteria namely education, experience, managerial skills, technical knowledge, communication. The ranking results show that the first rank with a final score of 0.045 was obtained by Candidate E, the second rank with a final value of 0.050 was obtained by Candidate K, and the third rank with a final value of 0.076 was obtained by Candidate J.